The fully-kinetic investigations on the ion acceleration mechanisms in an electron-driven magnetic nozzle. (1st May 2022) - Chen, Zhiyuan; Wang, Yibai; Ren, Junxue; Tang, Haibin; Wu, Peng; Li, Min
Abstract: A fully kinetic particle-in-cell study is conducted to investigate the ion acceleration mechanisms in an electron-driven magnetic nozzle. All five powers contributing to the axial kinetic energy of ions are derived and evaluated under different magnetic field strength and inlet density profiles. Among them, the electrothermal and electromagnetic acceleration contributes over 98% of the total accelerating power. The dominating acceleration mechanism is found to be the electrothermal acceleration, covering two thirds of the axial accelerating power in the electron-driven magnetic nozzle. The electromagnetic mechanism is found to originate from four sources, among which the major accelerating and decelerating one are the diamagnetic acceleration driven by radial gradient of electron pressure and the E × B mechanism due to the inward ion detachment. The power induced by the viscous-stress of electrons contributes 14%–23% of the decelerating power, indicating the non-negligible influence of finite electron Larmor radius effect on the ion acceleration. Results indicates that the net effect of electromagnetic mechanism can even be decelerating when the magnetic field is too high with a uniform inlet. Finally, the conversion efficiency from the inlet thermal energy to the ion axial kinetic energy is derived and evaluated, which can reach as high as 65.0% under 0.25 T with a Gaussian-profile inlet. Raising the magnetic field to 0.75 T or a uniform inlet will decrease the conversion efficiency.